2008
DOI: 10.1186/1746-1596-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated angiogenesis in B-chronic lymphocytic leukemia: Morphologic, immunohistochemical, and flow cytometric evidence

Abstract: Background: The extent of enhanced bone marrow angiogenesis in chronic lymphocytic leukemia (CLL) and relationship to proangiogenic factors and prognostic indicators is largely unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 34 publications
4
52
0
1
Order By: Relevance
“…62,63 To date, aberrant expression of HIF-1a and/or HIF-2a has been documented in cancers of the brain, colon, lung, breast, prostate, kidney, pancreas, cervix, bladder and ovary, [64][65][66][67][68][69] and overexpression of both HIFs has been found to indicate a highly aggressive disease phenotype associated with poor prognosis. [70][71][72][73][74][75][76] Whereas examination of aberrant HIF expression has largely been restricted to solid tumors, recent studies have reported that HIF-1a and HIF-2a are also overexpressed in hematological malignancies such as diffuse large B-cell lymphoma, 77,78 chronic lymphocytic leukemia 79 and acute lymphoblastic leukemia. 80 Although HIF-1a and HIF-2a show 48% amino-acid sequence homology and have similar protein structures and oxygendependent mechanisms of regulation, there are a growing number of physiological and mechanistic differences between these proteins, which indicates that they possess distinct, nonredundant roles.…”
Section: Hypoxia and Cancermentioning
confidence: 99%
“…62,63 To date, aberrant expression of HIF-1a and/or HIF-2a has been documented in cancers of the brain, colon, lung, breast, prostate, kidney, pancreas, cervix, bladder and ovary, [64][65][66][67][68][69] and overexpression of both HIFs has been found to indicate a highly aggressive disease phenotype associated with poor prognosis. [70][71][72][73][74][75][76] Whereas examination of aberrant HIF expression has largely been restricted to solid tumors, recent studies have reported that HIF-1a and HIF-2a are also overexpressed in hematological malignancies such as diffuse large B-cell lymphoma, 77,78 chronic lymphocytic leukemia 79 and acute lymphoblastic leukemia. 80 Although HIF-1a and HIF-2a show 48% amino-acid sequence homology and have similar protein structures and oxygendependent mechanisms of regulation, there are a growing number of physiological and mechanistic differences between these proteins, which indicates that they possess distinct, nonredundant roles.…”
Section: Hypoxia and Cancermentioning
confidence: 99%
“…17,18 Constitutive HIF-1a expression was suggested to induce vascular endothelial growth factor (VEGF) upregulation and neoangiogenesis. [19][20][21] However, because HIF-1a regulates a variety of other functions in solid tumors and hematologic malignancies, 1,22,23 we asked whether HIF-1a also controlled other aspects of CLL pathogenesis.…”
Section: Hif-1a Regulates Chemotaxis and Adhesion To Stroma In Cllmentioning
confidence: 99%
“…The process of angiogenesis (new blood vessel formation from pre-existing vasculature) has been shown to be crucial for growth and metastasizing ability of solid tumors mainly by increasing the oxygen and nutrients supply to malignant cells [2]. Angiogenesis in "liquid" tumors was supposed to be less important, nevertheless numerous recent studies have shown enhanced angiogenesis in many hematological malignancies including chronic myeloid leukemia [3], acute myeloid leukemia [4], acute lymphocytic leukemia [5], and CLL [6][7][8]. It has been demonstrated that elevated markers of angiogenesis correlate with unfavorable prognosis of CLL [9][10][11].…”
mentioning
confidence: 99%